Doctors' perspectives towards a bedside aminoglycoside therapeutic drug monitoring service: a collaboration between pharmacy and clinical pharmacology. (June 2015) - Phillips, Cameron J.; Chee, Celine T. L.; Eaton, Vaughn S.; Woodman, Richard J.; Mangoni, Arduino A.
Abstract Background A computerised area‐under‐the‐curve aminoglycoside therapeutic drug monitoring (A‐TDM) and dosing service was implemented at Flinders Medical Centre. Aim To assess attitudes and perceptions of junior medical officers and A‐TDM service providers towards the use and impact of A‐TDM. Methods An electronic survey was sent to junior medical officers containing questions on: A‐TDM awareness, impact on dosing, duration of therapy, minimisation of toxicity and the effect of provision of the service on knowledge of TDM principles. To determine whether respondents also had generally negative or positive attitudes, we used K‐means cluster analysis. A‐TDM service providers were also surveyed. Results From 145 junior medical officers contacted, 49 (33%) responded: 34 interns and 15 residents. The majority of officers provided generally positive responses, with 38 stating that they were aware of A‐TDM, 17 that it often assisted in their patient management, 34 that it improved optimal dosing, 22 that it improved duration, 32 that it improved toxicity minimisation and 33 that it improved their understanding of TDM principles. Cluster analysis produced a positive attitudes group (n = 35) and a negative attitudes group (n = 14) with significantly different responses for each of the six questions (p < 0.01 for each), indicating consistently different attitudes towards the service. Twelve of thirteen A‐TDM service providers responded: eight pharmacy and four medical, reporting positive attitudes towards A‐TDM on treatment efficacy (n = 11), dose optimisation (n = 11) and patient safety (n = 12). Conclusion A significant proportion of respondents were aware of A‐TDM principles and demonstrated favourable attitudes towards its use for dose optimisation and for minimising toxicity.